COMPETITIVE ADVANTAGES OF USING INTELLECTUAL CAPITAL - R. V. Faisullin; O. V. Abasheva; I. I. Chichenkov; A. I. Rokov (Вестник университета)
Industrial relations are becoming more complex every day, which is facilitated by economic development in the context of globalization. These circumstances make it necessary to achieve a level of competitiveness that corresponds to the industry and allows you to achieve leadership positions in the market. At present, the main factor of production that affects the competitiveness of the industry is intellectual capital. Introduction of intelligent technologies in production activities allows you to maximize production efficiency, which reflects the relevance of this research. It is necessary to study the possibility of achieving competitiveness at the industry level, for it has been proposed to consider the territorial development of intellectual capital, analyse existing trends in the process of intellectualization, present the advantages of the introduction of intelligent technologies in production and determine further prospects for studying the problem. This research is the preparation of a theoretical basis for analysing the industry situation of intellectualization and forecasting the possibilities of building an intelligent economy in the current unstable macroeconomic conditions.